Pengaruh Psychological Safety, Work-Life Balance, dan Job Satisfaction terhadap Work Engagement Karyawan - Irma Febriyani; Sri Isnowati (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The purpose of this study was to examine the effects of Psychological Safety, Work-Life Balance, and Job Satisfaction on Work Engagement among employees of KSPPS BMT Al Hikmah Semesta. This study employed a quantitative research method using a survey approach by distributing online questionnaires to employees of KSPPS BMT Al Hikmah Semesta through Google Forms. The research sample consisted of 66 respondents selected using a purposive sampling technique. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results of the study indicate that Psychological Safety has a positive and significant effect on Work Engagement. Job Satisfaction also has a positive and significant effect on Work Engagement, whereas Work-Life Balance does not have a significant effect on Work Engagement.